Additive for improving workability of concrete and preparation method thereof
By using admixtures of modified talc powder, nanosilicon dioxide and HYX-1 powder in concrete, the problem of poor lithogenic aggregate concrete and poor ease is solved, and better and ease and mechanical properties are achieved.
Patent Information
- Application Number
- CN202411669497.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-11
AI Technical Summary
When using different lithogenic aggregates to prepare concrete, it is difficult to effectively improve the ease of concrete, and problems such as separation and water leakage are prone to occur.
An admixture is used, including 60 to 80 parts of modified talc powder, 10 to 20 parts of nano silica and 10 to 20 parts of HYX-1 powder. The concrete and ease are improved by hydrophobic modification of the modified talc powder and the preparation of HYX-1 powder.
It significantly improves the and ease of concrete, reduces segregation and water leakage, improves the early strength and fluidity of concrete, and is suitable for different lithologic aggregates.
Smart Images

Figure BDA0005145442620000081 
Figure BDA0005145442620000082 
Figure BDA0005145442620000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building material concrete admixtures, and in particular relates to an admixture for improving the workability of concrete and a preparation method and use method thereof. Background Art
[0002] At present, the construction of hydropower projects has put forward higher environmental protection requirements, so the engineering concrete aggregates are usually made of local excavated materials. The pumped storage power station is located in a remote area with complex geological conditions. The excavated materials of the project are usually of special lithology. The concrete aggregates prepared from them are usually quite different from the high-quality limestone aggregates in the past. Some sandstone aggregates made from parent rocks with layered structures usually have problems such as poor grading and poor particle shape, which may lead to poor workability of concrete.
[0003] The workability of concrete is also called workability. Concrete with good workability is easy to mix, transport and pour, which can greatly improve construction efficiency. Concrete with good workability is easy to compact, which can reduce voids and bubbles, thereby improving the strength and durability of concrete. At the same time, good workability can also ensure that concrete is not prone to segregation and bleeding during the pouring process, ensuring the stability of construction quality.
[0004] The lithology of concrete aggregates prepared from excavated materials is usually special, and there are problems such as incompatibility with admixtures. For example, when adjusting the workability through water reducers, the dosage may be too low due to stone powder adsorption and cannot be effective. Once the dosage exceeds a certain limit, it is very easy to cause segregation and bleeding. Therefore, it is necessary to develop an admixture that is better applicable to aggregates of different lithologies and improves the workability of concrete. Summary of the invention
[0005] The purpose of the present invention is to provide an admixture for improving the workability of concrete, a preparation method and a use method thereof, which can improve the workability of concrete with good applicability to aggregates of different lithologies.
[0006] According to the first aspect of the present invention, the present invention adopts the following technical solution:
[0007] An admixture for improving the workability of concrete comprises the following components: 60-80 parts of modified talc powder, 10-20 parts of nano silicon dioxide, and 10-20 parts of HYX-1 powder; wherein the modified talc powder is prepared by hydrophobic modification of talc powder, and the HYX-1 powder is prepared by drying after reacting gluconic acid, dodecylbenzenesulfonic acid, lithium hydroxide and calcium hydroxide in an aqueous solution.
[0008] Furthermore, the modification method of the modified talc powder is as follows: first, the dried talc is ground and passed through a 2000 mesh sieve to obtain a fine powder, and the powder is washed with deionized water and anhydrous ethanol respectively, and the washing times can be 1 time respectively; then, 60 to 100 parts of the washed powder are added to deionized water and ultrasonically dispersed for 1 to 3 minutes, the pH of the reaction system is adjusted to 4.0 to 5.0 using an acetic acid solution, and the temperature is increased to 60 to 90° C., 10 to 20 parts of a silane coupling agent KH-570 modification solution and ethanol are added and ultrasonically dispersed for 1 to 3 minutes, magnetically stirred at a rate of 10 to 20 r / min for 1 to 3 hours, centrifuged after the reaction is completed, and washed with anhydrous ethanol, and the washing times can be 3 times; finally, the washed centrifuge is dried at 65 to 80° C. for 8 to 12 hours to obtain a dry material, and the dry material is ground and passed through a 1000 mesh sieve to obtain a modified talc powder.
[0009] Furthermore, the preparation method of HYX-1 powder is as follows: first, by weight, dissolve 20 to 30 parts of lithium hydroxide in 500 parts of water, adjust the temperature to 20 to 40°C, add a mixed powder of gluconic acid-dodecylbenzenesulfonic acid in a mass ratio of 1:2 to 1:3 while stirring until the solution pH is 3.0 to 5.5, then add calcium hydroxide until the solution pH is 5.5 to 7.0, and after the reaction is completed, dry to obtain HYX-1 powder, and the drying temperature can be 105°C.
[0010] Preferably, the nano-silicon dioxide is hydrophilic nano-silicon dioxide, with a particle size of no more than 50 nm and a purity of no less than 99.0%.
[0011] Preferably, the purity of the raw materials for preparing HYX-1 powder, gluconic acid, dodecylbenzenesulfonic acid, lithium hydroxide and calcium hydroxide, is not less than 98%, and the chloride ion content in the impurities does not exceed 0.01%.
[0012] On the other hand, the present invention provides a method for preparing the above-mentioned admixture for improving the workability of concrete, the preparation method comprising: mechanically mixing 60 to 80 parts by weight of modified talc powder, 10 to 20 parts of nano-silicon dioxide, and 10 to 20 parts of HYX-1 powder in a stirrer for 20 to 30 minutes to obtain the admixture for improving the workability of concrete.
[0013] On the other hand, the present invention provides a method for using the above-mentioned admixture for improving the workability of concrete, wherein the admixture is added during the dry mixing process of concrete, and the amount of the admixture is 0.5 to 2.0 kg per cubic meter of concrete.
[0014] The invention discloses an admixture for improving the workability of concrete. The admixture increases the physical restraint effect on water and reduces the segregation and bleeding phenomena by adding hydrophobic modified flaky talc particles with high specific surface area. The hydrophobicity of the surface enables the mixture to maintain a certain fluidity during the stress process. At the same time, the part of the flaky talc floating on the concrete surface has the function of reducing water evaporation. Nano-silicon dioxide has the function of improving the transition zone of the aggregate interface, thereby improving the early strength of the concrete. The slump-preserving effect of gluconate ions in LDX-1 powder and the penetration effect of lithium ions on the hydration film can improve the fluidity of the concrete. The dodecylbenzenesulfonate ions can introduce tiny bubbles and increase the volume of the cement paste, thereby improving the workability of the concrete.
[0015] Compared with the prior art, the present invention has the following significant advantages: (1) The present invention improves the bleeding and segregation of concrete by adding modified talcum powder, and reduces the evaporation of water on the surface of concrete; (2) The nano-silicon dioxide used in the present invention has the function of improving the transition zone of the aggregate interface, and can improve the strength of concrete; (3) The lithium ions in the LDX-1 powder of the present invention can penetrate the hydration membrane, the gluconate ions have a collapse-preserving effect, and the dodecylbenzenesulfonate ions can introduce tiny bubbles, increase the volume of the slurry, and thus improve the workability of the concrete. (4) The components of the present invention have a synergistic effect. The inducing effect and slurry lifting effect of the LDX-1 powder avoid the problem of decreased fluidity caused by excessive modified talcum powder. At the same time, the strengthening effect of nano-silicon dioxide avoids the problem of early strength decrease caused by the slow setting effect of LDX-1, thereby improving the workability and ensuring that the mechanical properties do not decrease. (5) The present invention can improve the fluidity of concrete while improving the bleeding and segregation of concrete, and has good adaptability to concrete with different lithology aggregates. DETAILED DESCRIPTION
[0016] Example 1
[0017] The present embodiment provides an admixture for improving the workability of concrete, characterized in that the admixture comprises the following components: by weight, 70 parts of modified talc powder, 15 parts of nano-silicon dioxide, and 15 parts of HYX-1 powder; wherein the modified talc powder is obtained by hydrophobic modification of talc powder, and the HYX-1 powder is obtained by reacting gluconic acid, dodecylbenzenesulfonic acid, lithium hydroxide, and calcium hydroxide in an aqueous solution and then drying.
[0018] The preparation method of the additive in this embodiment is as follows: by weight, 70 parts of modified talc powder, 15 parts of nano-silicon dioxide, and 15 parts of HYX-1 powder are mechanically mixed in a stirrer for 20 minutes to 30 minutes to obtain an additive.
[0019] The modification method of the modified talc is as follows: first, the dried talc is ground and passed through a 2000 mesh sieve to obtain a fine powder, and the powder is washed once with deionized water and anhydrous ethanol respectively; then, 60 to 100 parts of the washed powder are added to deionized water and ultrasonically dispersed for 1 to 3 minutes, the pH of the reaction system is adjusted to 4.0 to 5.0 with an acetic acid solution, and the temperature is increased to 60 to 90° C., 10 to 20 parts of a silane coupling agent KH-570 modification solution and ethanol are added and ultrasonically dispersed for 1 to 3 minutes, magnetically stirred at a rate of 10 to 20 r / min for 1 to 3 hours, centrifuged after the reaction is completed, and washed three times with anhydrous ethanol; finally, the washed centrifuge is dried at 65 to 80° C. for 8 to 12 hours to obtain a dry material, the dry material is ground and passed through a 1000 mesh sieve to obtain a modified talc powder.
[0020] The preparation method of HYX-1 powder is as follows: first, by weight, dissolve 20 parts of lithium hydroxide in 500 parts of water, adjust the temperature to 20-40°C, add a mixed powder of gluconic acid-dodecylbenzene sulfonic acid at a mass ratio of 1:2 while stirring until the solution pH is 3.0-5.5, then add calcium hydroxide until the solution pH is 5.5-7.0, and after the reaction is completed, dry at 105°C to obtain HYX-1 powder. The purity of the raw materials gluconic acid, dodecylbenzene sulfonic acid, lithium hydroxide, and calcium hydroxide is not less than 98%, and the chloride ion content in the impurities does not exceed 0.01%.
[0021] This embodiment provides a concrete with improved workability, wherein an admixture is added during the dry mixing process of the concrete, and the admixture is added in an amount of 0.5 kg, 1.0 kg and 2.0 kg per cubic meter of concrete. Ordinary concrete includes the following components: cement, water, sand, small stones (5-20 mm), large stones (20-40 mm), and a water reducing agent.
[0022] Example 2
[0023] The present embodiment provides an admixture for improving the workability of concrete, characterized in that the admixture comprises the following components: by weight, 60 parts of modified talc powder, 20 parts of nano-silicon dioxide, and 20 parts of HYX-1 powder; wherein the modified talc powder is obtained by hydrophobic modification of talc powder, and the HYX-1 powder is obtained by reacting gluconic acid, dodecylbenzenesulfonic acid, lithium hydroxide, and calcium hydroxide in an aqueous solution and then drying.
[0024] The preparation method of the additive in this embodiment is as follows: by weight, 60 parts of modified talc powder, 20 parts of nano-silicon dioxide, and 20 parts of HYX-1 powder are mechanically mixed in a stirrer for 20 minutes to 30 minutes to obtain the additive.
[0025] The modification method of the modified talc is as follows: first, the dried talc is ground and passed through a 2000 mesh sieve to obtain a fine powder, and the powder is washed once with deionized water and anhydrous ethanol respectively; then, 60 to 100 parts of the washed powder are added to deionized water and ultrasonically dispersed for 1 to 3 minutes, the pH of the reaction system is adjusted to 4.0 to 5.0 with an acetic acid solution, and the temperature is increased to 60 to 90° C., 10 to 20 parts of a silane coupling agent KH-570 modification solution and ethanol are added and ultrasonically dispersed for 1 to 3 minutes, magnetically stirred at a rate of 10 to 20 r / min for 1 to 3 hours, centrifuged after the reaction is completed, and washed three times with anhydrous ethanol; finally, the washed centrifuge is dried at 65 to 80° C. for 8 to 12 hours to obtain a dry material, the dry material is ground and passed through a 1000 mesh sieve to obtain a modified talc powder.
[0026] The preparation method of HYX-1 powder is as follows: first, by weight, dissolve 20 parts of lithium hydroxide in 500 parts of water, adjust the temperature to 20-40°C, add a mixed powder of gluconic acid-dodecylbenzene sulfonic acid at a mass ratio of 1:2 while stirring until the solution pH is 3.0-5.5, then add calcium hydroxide until the solution pH is 5.5-7.0, and after the reaction is completed, dry at 105°C to obtain HYX-1 powder. The purity of the raw materials gluconic acid, dodecylbenzene sulfonic acid, lithium hydroxide, and calcium hydroxide is not less than 98%, and the chloride ion content in the impurities does not exceed 0.01%.
[0027] This embodiment provides a concrete with improved workability, wherein an admixture is added during the dry mixing process of the concrete, and the admixture is added in an amount of 0.5 kg, 1.0 kg and 2.0 kg per cubic meter of concrete. Ordinary concrete includes the following components: cement, water, sand, small stones (5-20 mm), large stones (20-40 mm), and a water reducing agent.
[0028] Example 3
[0029] The present embodiment provides an admixture for improving the workability of concrete, characterized in that the admixture comprises the following components: by weight, 80 parts of modified talc powder, 10 parts of nano-silicon dioxide, and 10 parts of HYX-1 powder; wherein the modified talc powder is obtained by hydrophobic modification of talc powder, and the HYX-1 powder is obtained by reacting gluconic acid, dodecylbenzenesulfonic acid, lithium hydroxide, and calcium hydroxide in an aqueous solution and then drying the reacted talc powder.
[0030] The preparation method of the additive in this embodiment is as follows: by weight, 80 parts of modified talc powder, 10 parts of nano-silicon dioxide, and 10 parts of HYX-1 powder are mechanically mixed in a stirrer for 20 minutes to 30 minutes to obtain an additive.
[0031] The modification method of the modified talc is as follows: first, the dried talc is ground and passed through a 2000 mesh sieve to obtain a fine powder, and the powder is washed once with deionized water and anhydrous ethanol respectively; then, 60 to 100 parts of the washed powder are added to deionized water and ultrasonically dispersed for 1 to 3 minutes, the pH of the reaction system is adjusted to 4.0 to 5.0 with an acetic acid solution, and the temperature is increased to 60 to 90° C., 10 to 20 parts of a silane coupling agent KH-570 modification solution and ethanol are added and ultrasonically dispersed for 1 to 3 minutes, magnetically stirred at a rate of 10 to 20 r / min for 1 to 3 hours, centrifuged after the reaction is completed, and washed three times with anhydrous ethanol; finally, the washed centrifuge is dried at 65 to 80° C. for 8 to 12 hours to obtain a dry material, the dry material is ground and passed through a 1000 mesh sieve to obtain a modified talc powder.
[0032] The preparation method of HYX-1 powder is as follows: first, by weight, dissolve 20 parts of lithium hydroxide in 500 parts of water, adjust the temperature to 20-40°C, add a mixed powder of gluconic acid-dodecylbenzene sulfonic acid at a mass ratio of 1:2 while stirring until the solution pH is 3.0-5.5, then add calcium hydroxide until the solution pH is 5.5-7.0, and after the reaction is completed, dry at 105°C to obtain HYX-1 powder. The purity of the raw materials gluconic acid, dodecylbenzene sulfonic acid, lithium hydroxide, and calcium hydroxide is not less than 98%, and the chloride ion content in the impurities does not exceed 0.01%.
[0033] This embodiment provides a concrete with improved workability, wherein an admixture is added during the dry mixing process of the concrete, and the admixture is added in an amount of 0.5 kg, 1.0 kg and 2.0 kg per cubic meter of concrete. Ordinary concrete includes the following components: cement, water, sand, small stones (5-20 mm), large stones (20-40 mm), and a water reducing agent.
[0034] Example 4
[0035] The present embodiment provides an admixture for improving the workability of concrete, characterized in that the admixture comprises the following components: by weight, 70 parts of modified talc powder, 10 parts of nano-silicon dioxide, and 20 parts of HYX-1 powder; wherein the modified talc powder is obtained by hydrophobic modification of talc powder, and the HYX-1 powder is obtained by drying after reacting gluconic acid, dodecylbenzenesulfonic acid, lithium hydroxide, and calcium hydroxide in an aqueous solution.
[0036] The preparation method of the additive in this embodiment is as follows: by weight, 70 parts of modified talc powder, 10 parts of nano-silicon dioxide, and 20 parts of HYX-1 powder are mechanically mixed in a stirrer for 20 minutes to 30 minutes to obtain the additive.
[0037] The modification method of the modified talc is as follows: first, the dried talc is ground and passed through a 2000 mesh sieve to obtain a fine powder, and the powder is washed once with deionized water and anhydrous ethanol respectively; then, 60 to 100 parts of the washed powder are added to deionized water and ultrasonically dispersed for 1 to 3 minutes, the pH of the reaction system is adjusted to 4.0 to 5.0 with an acetic acid solution, and the temperature is increased to 60 to 90° C., 10 to 20 parts of a silane coupling agent KH-570 modification solution and ethanol are added and ultrasonically dispersed for 1 to 3 minutes, magnetically stirred at a rate of 10 to 20 r / min for 1 to 3 hours, centrifuged after the reaction is completed, and washed three times with anhydrous ethanol; finally, the washed centrifuge is dried at 65 to 80° C. for 8 to 12 hours to obtain a dry material, the dry material is ground and passed through a 1000 mesh sieve to obtain a modified talc powder.
[0038] The preparation method of HYX-1 powder is as follows: first, by weight, dissolve 20 parts of lithium hydroxide in 500 parts of water, adjust the temperature to 20-40°C, add a mixed powder of gluconic acid-dodecylbenzene sulfonic acid at a mass ratio of 1:2 while stirring until the solution pH is 3.0-5.5, then add calcium hydroxide until the solution pH is 5.5-7.0, and after the reaction is completed, dry at 105°C to obtain HYX-1 powder. The purity of the raw materials gluconic acid, dodecylbenzene sulfonic acid, lithium hydroxide, and calcium hydroxide is not less than 98%, and the chloride ion content in the impurities does not exceed 0.01%.
[0039] This embodiment provides a concrete with improved workability, wherein an admixture is added during the dry mixing process of the concrete, and the admixture is added in an amount of 0.5 kg, 1.0 kg and 2.0 kg per cubic meter of concrete. Ordinary concrete includes the following components: cement, water, sand, small stones (5-20 mm), large stones (20-40 mm), and a water reducing agent.
[0040] Example 5
[0041] The present embodiment provides an admixture for improving the workability of concrete, characterized in that the admixture comprises the following components: by weight, 70 parts of modified talc powder, 20 parts of nano-silicon dioxide, and 10 parts of HYX-1 powder; wherein the modified talc powder is obtained by hydrophobic modification of talc powder, and the HYX-1 powder is obtained by drying after reacting gluconic acid, dodecylbenzenesulfonic acid, lithium hydroxide, and calcium hydroxide in an aqueous solution.
[0042] The preparation method of the additive in this embodiment is as follows: by weight, 70 parts of modified talc powder, 20 parts of nano-silicon dioxide, and 10 parts of HYX-1 powder are mechanically mixed in a stirrer for 20 minutes to 30 minutes to obtain the additive.
[0043] The modification method of the modified talc is as follows: first, the dried talc is ground and passed through a 2000 mesh sieve to obtain a fine powder, and the powder is washed once with deionized water and anhydrous ethanol respectively; then, 60 to 100 parts of the washed powder are added to deionized water and ultrasonically dispersed for 1 to 3 minutes, the pH of the reaction system is adjusted to 4.0 to 5.0 with an acetic acid solution, and the temperature is increased to 60 to 90° C., 10 to 20 parts of a silane coupling agent KH-570 modification solution and ethanol are added and ultrasonically dispersed for 1 to 3 minutes, magnetically stirred at a rate of 10 to 20 r / min for 1 to 3 hours, centrifuged after the reaction is completed, and washed three times with anhydrous ethanol; finally, the washed centrifuge is dried at 65 to 80° C. for 8 to 12 hours to obtain a dry material, the dry material is ground and passed through a 1000 mesh sieve to obtain a modified talc powder.
[0044] The preparation method of HYX-1 powder is as follows: first, by weight, dissolve 20 parts of lithium hydroxide in 500 parts of water, adjust the temperature to 20-40°C, add a mixed powder of gluconic acid-dodecylbenzene sulfonic acid at a mass ratio of 1:2 while stirring until the solution pH is 3.0-5.5, then add calcium hydroxide until the solution pH is 5.5-7.0, and after the reaction is completed, dry at 105°C to obtain HYX-1 powder. The purity of the raw materials gluconic acid, dodecylbenzene sulfonic acid, lithium hydroxide, and calcium hydroxide is not less than 98%, and the chloride ion content in the impurities does not exceed 0.01%.
[0045] This embodiment provides a concrete with improved workability, wherein an admixture is added during the dry mixing process of the concrete, and the admixture is added in an amount of 0.5 kg, 1.0 kg and 2.0 kg per cubic meter of concrete. Ordinary concrete includes the following components: cement, water, sand, small stones (5-20 mm), large stones (20-40 mm), and a water reducing agent.
[0046] Comparative Example 1
[0047] Compared with Example 1, the difference of this comparative example is that the admixture for improving concrete workability provided in this comparative example does not add modified talc powder. Specifically, the admixture includes the following components: 15 parts of nano silicon dioxide and 15 parts of HYX-1 powder by weight.
[0048] By weight, 15 parts of nano-silicon dioxide and 15 parts of HYX-1 powder are mechanically mixed in a mixer for 20 to 30 minutes to obtain an admixture for improving the workability of concrete.
[0049] Comparative Example 2
[0050] Compared with Example 1, the difference of this comparative example is that the admixture for improving concrete workability provided in this comparative example does not add nano silicon dioxide. Specifically, the admixture includes the following components: 70 parts by weight of modified talc powder and 15 parts of HYX-1 powder.
[0051] By weight, 70 parts of modified talc powder and 15 parts of HYX-1 powder were mechanically mixed in a mixer for 20 to 30 minutes to obtain an admixture for improving the workability of concrete.
[0052] Comparative Example 3
[0053] Compared with Example 1, the difference of this comparative example is that the admixture for improving concrete workability provided in this comparative example does not add HYX-1 powder. Specifically, the admixture includes the following components: 70 parts by weight of modified talc powder and 15 parts of nano silicon dioxide.
[0054] Calculated by weight, 70 parts of modified talc powder and 15 parts of nano-silicon dioxide are mechanically mixed in a stirrer for 20 to 30 minutes to obtain an admixture for improving the workability of concrete.
[0055] Blank example
[0056] The blank case does not contain any admixture to improve the workability of concrete.
[0057] Concrete workability test
[0058] The performance of the above-mentioned embodiments and comparative examples was tested through concrete tests, wherein the cement was Conch P·O42.5 ordinary Portland cement, the fly ash was Grade II fly ash, the water reducer was polycarboxylic acid water reducer, and the sandstone aggregate was sandstone aggregate with poor particle shape, and the mix ratio was shown in Table 1.
[0059] Table 1 Concrete mix ratio
[0060]
[0061] The admixture dosage (0.5, 1.0, 2.0 kg) of the admixture for improving the workability of concrete in Example 1 was added to the concrete, and the admixture without the admixture for improving the workability of the concrete was used as a blank sample. The workability of the concrete mixture was tested in accordance with GB T 50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures".
[0062] Table 2 Concrete crack resistance test results of Example 2
[0063]
[0064]
[0065] From the above test results, it can be seen that the workability of the blank group sandstone slate aggregate concrete is poor, with segregation, water seepage and exposed stone phenomena. After adding 0.5kg, 1.0%kg and 2.0kg of concrete workability improving admixtures, the water seepage rate was reduced by 10.1%, 12.2% and 9.3% respectively, greatly improving the workability of the concrete mixture.
[0066] The admixtures for improving the workability of concrete in each embodiment and comparative example were added to the concrete at a dosage of 1 kg, and the admixtures for improving the workability of concrete were used as blank samples. The crack resistance of concrete under flat plate restraint was tested according to GB / T 50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete". The mix workability of concrete was tested according to GBT50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures", and the test results are shown in Table 3.
[0067] Table 3 Concrete workability test results
[0068]
[0069]
[0070] The above test results show that the workability of the blank group is poor, and there is a serious phenomenon of segregation and bleeding. Compared with the blank group, the concrete after the embodiment no longer has bleeding, segregation, and stone exposure, the concrete workability is significantly improved, and the slump and expansion are improved to a certain extent, indicating that the concrete construction performance is improved. The air content of the concrete has increased to a certain extent, which is due to the introduction of tiny bubbles by the LDX-1 powder, which helps to improve the fluidity of the concrete. At the same time, due to the improvement of the interface transition zone by nano-silicon dioxide, the 3d and 7d compressive strengths have been improved to a certain extent. Compared with the embodiment, comparative example 1 is not mixed with modified talcum powder, and there is still a lot of bleeding. At the same time, the slow setting and air entraining effect of excessive LDX-1 powder leads to a decrease in compressive strength. Comparative example 2 is not mixed with nano-silicon dioxide, and the slump and expansion are improved, indicating that the fluidity has improved, but there is slight bleeding, and the strength has decreased. Comparative example 3 is not mixed with LDX-1 powder, and the workability is improved, but there is still stone exposure. This shows that the admixture of the embodiment has the best effect of improving the workability of concrete, and the improvement effect is best when the admixture is 1 kg.
[0071] The above are all preferred embodiments of the present invention, and are not intended to limit the protection scope of the present application. Any modifications, equivalent substitutions, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An admixture for improving the workability of concrete, characterized in that: The additive comprises the following components: by weight, 60 to 80 parts of modified talc powder, 10 to 20 parts of nano silicon dioxide, and 10 to 20 parts of HYX-1 powder; wherein the modified talc powder is prepared by hydrophobic modification of talc powder, and the HYX-1 powder is prepared by drying after reacting gluconic acid, dodecylbenzenesulfonic acid, lithium hydroxide, and calcium hydroxide in an aqueous solution.
2. The admixture for improving the workability of concrete according to claim 1, characterized in that: The preparation method of modified talc powder is as follows: first, dry talc is ground and then passed through a 2000 mesh sieve to obtain fine powder, and the powder is washed with deionized water and anhydrous ethanol respectively; then, 60 to 100 parts of the washed powder are added into deionized water and ultrasonically dispersed for 1 to 3 minutes, an acetic acid solution is used to adjust the pH of the reaction system to 4.0 to 5.0, and the temperature is increased to 60 to 90° C., 10 to 20 parts of a silane coupling agent KH-570 modified solution and ethanol are added and ultrasonically dispersed for 1 to 3 minutes, magnetic stirring is performed at a rate of 10 to 20 r / min for 1 to 3 hours, centrifugation is performed after the reaction is completed, and anhydrous ethanol is used for washing; finally, the washed centrifuge is dried at 65 to 80° C. for 8 to 12 hours to obtain a dry material, the dry material is ground and passed through a 1000 mesh sieve to obtain the modified talc powder.
3. The admixture for improving the workability of concrete according to claim 1, characterized in that: The nano silicon dioxide is a hydrophilic nano silicon dioxide with a particle size of no more than 50 nm and a purity of no less than 99.0%.
4. The admixture for improving the workability of concrete according to claim 1, characterized in that: The preparation method of the HYX-1 powder is as follows: firstly, by weight, dissolving 20 to 30 parts of lithium hydroxide in 500 parts of water, adjusting the temperature to 20 to 40° C., adding a mixed powder of gluconic acid-dodecylbenzenesulfonic acid in a mass ratio of 1:2 to 1:3 while stirring until the pH value of the solution is 3.0 to 5.5, then adding calcium hydroxide until the pH value of the solution is 5.5 to 7.0, and drying after the reaction is completed to obtain the HYX-1 powder.
5. The admixture for improving the workability of concrete according to claim 4, characterized in that: The purity of the raw materials gluconic acid, dodecylbenzenesulfonic acid, lithium hydroxide and calcium hydroxide is not less than 98%, and the chloride ion content in the impurities does not exceed 0.01%.
6. The admixture for improving the workability of concrete according to any one of claims 1 to 5, characterized in that: Its usage is: add admixtures during the dry mixing process of concrete, with the dosage being 0.5 to 2.0 kg per cubic meter of concrete.
7. The method for preparing the admixture for improving the workability of concrete according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: mechanically mixing 60 to 80 parts by weight of modified talc powder, 10 to 20 parts of nano silicon dioxide and 10 to 20 parts of HYX-1 powder in a stirrer for 20 to 30 minutes to obtain an admixture for improving the workability of concrete.